Integrative review of health education and evaluation models - Moimaz, Suzely Adas Saliba [UNESP]; Tellez, Maria Elizabeth Peña [UNESP]; De Paiva Gomes Fernandes, Eder Akydawan [UNESP]; Saliba, Tânia Adas [UNESP] (Revista Meta - Avaliacao, 2023)
Health education programs encourage the adoption of healthy behaviors by the population, but the results are not always evaluated. The objective was to identify the methods used in the evaluation of health education programs. An integrative review was carried out, based on the recommendations of the PRISMA model, in the following databases: VHL Regional Portal, SciELO, Embase, PubMed and Cochrane. Of the 1745 articles found, 1610 were excluded due to lack of clarity in the description of the methodology, leaving 20 studies, of which 17 were oral health programs and 3 were general health programs; In the selected studies, oral hygiene habits, caries index, plaque index, gingival changes, frequency of brushing and health knowledge were evaluated. Of the total, 18 showed significant changes with satisfactory results in actions aimed at improving oral health. The most common method to evaluate the results was the questionnaire. The interview, oral and general examination, and the focus group technique were used on a smaller scale; this review may be useful in future research in the area, opening new lines of knowledge when evaluating educational programs.
Revisión integradora de educación en salud y modelos evaluativos
Revisão integrativa da educação em saúde e modelos avaliativos
Keywords: Education evaluation; Educational programs; Health evaluation; Oral health; Students